Efektivitas Konseling Kelompok Teknik Rational Emotive Imagery dan Homework Assigment untuk Meningkatkan Tanggung Jawab Remaja - Suryatmoko, Slamet (Prosiding University Research Colloquium, 2021)
Because of the consequences of low youth responsibility in Menayu Hamlet, Menayu Village, Muntilan, Magelang, this study was performed on the youth of Menayu Hamlet, Menayu Village, Muntilan, Magelang. The purpose of this study is to see whether group counseling using the Rational Emotive Imagery Technique and the Homework Assignment Technique can help youth in Menayu Hamlet, Menayu Village, Muntilan, Magelang get more responsible. With a Randomized Pretest Posttest Comparison Group Design research design, this type of study is a true experiment. The subjects in this research were 10 teens whose are divided into 2 groups: 5 teenagers in the Rational Emotive Imagery Technique group and 5 teenagers in the Homework Assignment Technique group. Sample was executed using a random sampling technique. With the help of SPSS 25, the data was analyzed using One Way Anova parametric analysis. The therapy of group counseling services occurs over the course of nine meetings. The findings of this study show that group counseling using the Rational Emotive Imagery Technique and the Homework Assignment Technique can help teenagers are becoming more responsible. The study's findings were supported by the One Way Anova Parametric Statistics test, which returned a probability considerable value of 0.001. There is a difference in the average score of the responsibility questionnaire between the two classes after testing the data. The experimental group 1 had a percentage increase of 10.26%, whereas the experimental group 2 have seen a percentage increase of 12.21%. This study found that group counseling using the Homework Assignment technique is more effective than group counseling using the Rational Emotive Imagery technique in improving responsibility.